PENGEMBANGAN MEDIA KAYU JATI BEREKOR DALAM PEMBELAJARAN LEMPAR LEMBING PADA SISWA KELAS VIII DI SMP NEGERI 1 SALE KECAMATAN SALE KABUPATEN REMBANG TAHUN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2013)
The purpose of This study by the actual form of the javelin has a big risk if used in javelin learning in schoolSMP Negeri 1 Sale a mini field conditions so that here the researcher makes media as a substitute for teakwood tailed javelin javelin in learning outcomes by utilizing existing natural around the school in the form ofwood jati.Metode this study refers to the model of the development of Borg & Gallyang havedimodifikasi.Pengumpulan using questionnaire data were obtained from the evaluation of the expert penjasdanpembelajaran , a small test group ( 12 students ) , and a field test ( 30 students ) . mengenaikualitasassessment data in the form of products , suggestions for improvement of the product , and the results of thequestionnaires by students . The data analysis technique used is descriptive percentage to reveal aspects ofpsychomotor , cognitive and affective student after using the product .From the test results obtained by the expert evaluation data , expert penjas 93 % ( very good ) , a study 96 % (very good ) , a small test group 77 % ( good ) , and a field test 85 % ( very good ) . From the available data itcan be concluded that the model of development of the caudate teak media can be used in teaching studentsjavelin at SMP N 1 Sale Rembang .